Delivery of health and nutrition services in COVID-19 India - Avula, Rasmi (2020)
Rasmi Avula POLICY SEMINAR Virtual Event - No backsliding: How can we re-orient food systems and health systems to protect nutrition and healthy diets in the context of COVID-19? Co-Organized by IFPRI and the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) MAY 28, 2020 - 09:30 AM TO 11:00 AM EDT